FEATURES OF TEACHING HUMANITIES IN HIGHER EDUCATION INSTITUTIONS FOR FUTURE SPECIALISTS IN HOTEL AND RESTAURANT BUSINESS AND TOURISM - Zelman, Lesia; Mykytenko, Oleksandr (Global Prosperity, 2021)
We have considered the features of professional training of specialists in the hotel and restaurant business and tourism. In the analysis of the curriculum, we appear to find a place in the training of future specialists in hotel and restaurant business and tourism in the study of humanities, namely: "Ukrainian language for professional purposes", "World culture and art", "Foreign language for professional orientation", "Fundamentals of professional ethics and culture of communication", and other. During the course, participants of the educational process must make efforts to form a communicative culture, critical thinking and aesthetics of speech. Future masters of hotel and restaurant business and tourism must be at a high level of management of communicative culture and content to think critically. The humanities cycle subjects basing on the text, with the help of which educational activities are carried out, training of future specialists of hotel and restaurant enterprises and tourism takes part in professional texts that help students accumulate professional terminology and form professional skills. We concluded that introducing elements of the dual system of education is a positive trend in the training of hotel and restaurant professionals and tourism. Students can assimilate and improve communication culture, see bottlenecks and make an effort to correct and improve themselves.